Very elderly patients on haemodialysis: Evolution and its relation with comorbidities - Bento,Claudia (2014)
Introduction: The population ageing has conditioned a progressive increase of very old patients on haemodialysis. These patients present multiple comorbidities that worsen the prognosis in dialysis and have an impact on their quality of life. Material and Methods: A retrospective observational study was performed, analysing all patients over 80 years of age that started regular haemodialysis between January 2004 and December 2011. The comorbidities were stratified using the Charlson score and correlated with mortality. Survival analysis was performed with Kaplan-Meier curves. Results: Fifty-nine patients were included, 35 females and 24 males, with a mean age of 84 ± 3 years. At the start of dialysis, the estimated glomerular filtration rate calculated using the modification of diet in renal disease (MDRD) formula was 10.8 ± 2.5 mL/min /1.73 m2. The initial Charlson score was 8 ± 3 and became higher at the end of follow-up (11.5 ± 2.9; p < 0.01). A Charlson score ≥ 8 was associated with more hospitalization days (878 vs. 360; p < 0.005). The survival rate was 56 % at 12 months and 31% at 24 months. The mortality rate at the end of follow-up (20.4 ± 15.7 months) was 55.9%, with a mortality rate of 27.3% at 3 months. The patients with early death presented a higher Charlson score (13.0 ± 1.7 vs. 6.4 ± 1.2; p < 0.01) at the beginning of dialysis. Conclusion: The benefits of dialysis in survival and quality of life in very elderly patients have been questioned. In our series, more than 1/4 of the patients died in the first 3 months of dialysis, corresponding to higher comorbidity scores. The use of comorbidity scores like the Charlsons may assist in the assessment of the short-term prognosis, but the individualized decision should prevail in all cases.